Halal Certification Regulation on Health Products: A Global Comparative Study - Astiwara, Endy Muhammad (International Journal of Science and Society, 2023)
The growing global demand for halal-certified healthcare products has brought renewed attention to the regulatory frameworks governing halal certification in the pharmaceutical and health sectors. This study aims to analyze and compare halal certification regulations across various countries, identifying best practices, structural challenges, and opportunities for harmonization. The research synthesizes data from industry reports, regulatory documents, and academic studies, complemented by case studies that illustrate the successes and failures of implementation in key halal markets such as Indonesia, Malaysia, the Gulf Cooperation Council (GCC) countries, and selected Western nations used a qualitative-comparative methodology. Findings reveal that while some countries have established robust institutional mechanisms and comprehensive halal assurance systems, others face systemic limitations, including inconsistent standards, high certification costs, and shortages of halal-compliant raw materials. The study highlights the fragmented nature of global halal certification and the resulting barriers to international trade and consumer trust. A thematic analysis further identifies recurring issues such as regulatory ambiguity, inadequate auditor capacity, and consumer sentiment surrounding certification speed and transparency. The research underscores the urgency of promoting regulatory convergence and cross-border cooperation to support the growth of a trusted and inclusive halal healthcare ecosystem.